A self-supported gel filter membrane for dye removal with high anti-fouling and water flux performance. (26th June 2020) - Hu, Jiawei; Chen, Yi; Lu, Jiawei; Fan, Xiaokun; Li, Jie; Li, Zhihan; Zeng, Guangsheng; Liu, Wenyong
Abstract: Traditional polymer filtration membranes are easily polluted in operation. An interpenetrating polymer network (IPN) gel was designed as a self-supported filter membrane. This IPN gel was structured by a Ca 2+ crosslinked alginate network and a covalently crosslinked poly(acrylamide) network. Polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) was hybridised into the gel to optimise performance. Our research demonstrated that the uniform dispersion of PEG-POSS in the matrix improved membrane performance comprehensively due to its nanoscale and amphipathicity. The membranes showed well mechanical properties and sewage treatment capacity. Under the operation pressure 2 bar, the water flux of membranes could keep 11.7 L m −2  h −1 in long-term use. When dealing with the high concentration (500 mg L −1 ) of Methylene blue and Congo red solution, the rejection of dye could reach 93% and 95% respectively. In anti-fouling experiments with 8000 mg L −1 protein emulsion as the fouling source, the membranes keep over 80% initial flux after 10 times of water-emulsion cycle. Graphical abstract: Image 1 Highlights: A self-supported POSS hybrid hydrogel filter membrane with applicable water flux and mechanical property is provided. The membrane has excellent rejection ratio towards cationic and anionic dyes. The membrane has excellent anti-fouling performance and reusability after elution.